Effects of fatigue on postural control strategies during Biathlon shooting - A nonlinear approach - Buchecker, M.; Sattlecker, G.; Birklbauer, J.; Wegenkittl, S.; Lindinger, S.; Müller, E. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aim of the current exploratory research project was to test experienced biathletes of different performance squads while standing shooting at rest and after physical exercise and to evaluate resultant COP patterns by employing also "nonlinear" assessment techniques.